Regulação da maquinaria de reparo do DNA em paracoccidioides brasiliensis durante o estresse oxidativo. - Chaves, Alison Felipe Alencar [UNIFESP] (2019)
Paracoccidioidomycosis is a granulomatous disease caused by fungi of the genus Paracoccidioides and widely distributed in Latin America. The disease has high disabling potential and yet is still absolutely neglected. These fungi undergo cell differentiation induced by changes in temperature and this event is critical to the ability to cause disease. The knowledge of which molecular patterns of the fungus may be true virulence factors is still limited by the difficulties inherent to genetic manipulation of these fungi. Studies that have tried to understand these molecular aspects rely on the method of transformation mediated by Agrobacterium tumefaciens, a model that is highly costly in terms of time and resources and has low reproducibility. To overcome these barriers, we need to better understand the mechanisms of DNA repair used by the fungus. This is because the establishment of a knockout strain depends on the occurrence of homologous recombination events. The present study showed that P. brasiliensis has a conserved repair machinery to respond to DNA double strand breaks and that this machinery is also responsive to oxidative stress. These double-strand breaks repair pathways communicate with the Ras GTPase and Hog1 Map kinase pathways. In addition, inhibition of the non-homologous end joining (NHEJ) mediated repair pathway has been observed to provide a protective response to P. brasiliensis yeasts during a normally lethal oxidative stress condition for the fungus. Perhaps, this event is related to the greater efficiency of the repair by homologous recombination induced by the inhibition of NHEJ. Finally, it was observed that the combination of the damping of the NHEJ pathway, through the inhibition of Dn4 or GSK3, together with the induced oxidative stress can increase the efficiency of transformation processes in yeasts of P. brasiliensis. Altogether, these findings broaden the repertoire of possibilities to achieve the establishment of a knockout strain in P. brasiliensis.